Groundnut: As Influenced by Sowing Window and Integrated Nitrogen Management (INM) - Nayak, Ridhi Das (Current Research Progress in Agricultural Sciences Vol. 1, 2024)
Oilseeds are high-energy crops, thus they require a lot of major, secondary, and micronutrients. The nutrient removal rate varies greatly depending on crop productivity and soil fertility. The sowing date is one of the most essential parameters that influence groundnut growth and yield. Groundnut is a crop that needs precise environmental conditions to grow and develop properly, and its reaction to sowing dates might vary depending on the local climate, soil type, and other factors. Growing plants in their natural habitat with a normal temperature range when exposed to high temperatures without acclimation can cause serious damage to the plant, so improving thermotolerance acquisition ability is critical for plants. Improvement in the delayed breakdown of organic manure and increased soil biological activity could explain the improvement in the available nutrient status of the soil with the introduction of vermicompost alone or in combination with chemical fertilizer.